Hongyuyin attenuates intestinal fibrosis in ulcerative colitis in mice revealed by transcriptomic and network pharmacology analyses - Qin Qin; Qingjun Dong; Yan Pan; Chen Wang; Jingen Lu (Scientific Reports)
Abstract Ulcerative colitis (UC) is a chronic, idiopathic inflammatory disease affecting the gastrointestinal tract. Hongyuyin (HYY), a traditional Chinese botanical formulation, has been effectively treating UC for over three decades; however, its underlying biological mechanism of action in UC-associated intestinal fibrosis (IF) remains unclear. This study investigated the mechanisms of action of HYY on IF through in vivo experiments using a dextran sulfate sodium (DSS)-induced mouse colitis model. Clinical symptoms, colonic pathological damage, inflammation, and fibrosis were monitored across all groups. Both transcriptomic analysis and network pharmacology (NP) techniques were utilized to elucidate the mechanistic insights. HYY treatment substantially reduced inflammation, fibroblast activation, and collagen deposition in UC mice. KEGG analyses suggested that HYY treatment modulated multiple signaling pathways, notably the TNF, IL-17, and PI3K-Akt signaling pathways. Combined analysis identified the PI3K-Akt signaling pathway as a major contributor, with high enrichment factors and numerous enrichment genes involved (IL-6, CSF3, SPP1, AKT1, PIK3CA, and so on) in UC-associated IF. Western blotting confirmed significant reductions in both p-AKT/AKT and p-mTOR/mTOR ratios after HYY treatment. Collectively, HYY alleviates UC-associated IF by reducing the phosphorylation of PI3K-Akt pathway factors, thereby inhibiting fibroblast activation and collagen deposition. This research provides novel insights into HYY’s mechanism of action in UC-associated IF management.